2014
DOI: 10.1002/hbm.22455
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of human actions: Expertise and task‐related effects on neural activation of the action observation network

Abstract: The action observation network (AON) is supposed to play a crucial role when athletes anticipate the effect of others' actions in sports such as tennis. We used functional magnetic resonance imaging to explore whether motor expertise leads to a differential activation pattern within the AON during effect anticipation and whether spatial and motor anticipation tasks are associated with a differential activation pattern within the AON depending on participant expertise level. Expert (N=16) and novice (N=16) tenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 102 publications
12
66
0
Order By: Relevance
“…On the other hand, motor training might induce the automation of task performance and simplify the motor planning process, thereby decreasing activity in the PPC (e.g., Petrini et al, 2011). In the current study, motor experts showed a stronger PPC effect as compared with novices when performing trained actions (Bernardi et al, 2013;Pau et al, 2013), observing other people doing the (Haslinger et al, 2005), or predicting object movement on the basis of training experience (Balser et al, 2014). This is in line with the former view and implies that motor experts, after intensive training, may be better at integrating somatosensory, auditory, and visual information in location monitoring and motor adjustment (Baeck et al, Note: The coordinates of the effects are in the Talairach space .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…On the other hand, motor training might induce the automation of task performance and simplify the motor planning process, thereby decreasing activity in the PPC (e.g., Petrini et al, 2011). In the current study, motor experts showed a stronger PPC effect as compared with novices when performing trained actions (Bernardi et al, 2013;Pau et al, 2013), observing other people doing the (Haslinger et al, 2005), or predicting object movement on the basis of training experience (Balser et al, 2014). This is in line with the former view and implies that motor experts, after intensive training, may be better at integrating somatosensory, auditory, and visual information in location monitoring and motor adjustment (Baeck et al, Note: The coordinates of the effects are in the Talairach space .…”
Section: Discussionmentioning
confidence: 52%
“…Recent research has indicated that motor expertise influences the brain activity of motor execution (e.g., Bernardi et al, 2013;Meister et al, 2005), motor observation (e.g., Kim et al, 2011;Olsson & Lundström, 2013;Pilgramm, Lorey, Stark, Munzert, Vaitl, & Zentgraf, 2010;Stout et al, 2011;, motor imagery or planning (e.g., Chang et al, 2011;Milton, Solodkin, Hlustík, & Small, 2007;Wei & Luo, 2010), motor prediction (e.g., Abreu et al, 2012;Balser et al, 2014;, and even the comprehension of action language (Beilock, Lyons, MattarellaMicke, Nusbaum, & Small, 2008;Lyons et al, 2010;Tomasino, Maieron, Guatto, Fabbro, & Rumiati, 2013). However, the findings are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, during action prediction, externally evoked activation of the motor cortex was shown to lead to an increase in the amplitude of muscles involved in the observed action relative to baseline (Aglioti et al, 2008;Tomeo et al, 2012). Third, areas of the brain known to be part of the action observation network also differentiated across novice and experts (in tennis) during prediction of action outcomes (Balser et al, 2014). Fourth, action predictions also improved following training without vision on a dart-throwing task (Mulligan and Hodges, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…McRobert, Ward, Eccles, & Williams, 2011;Roca, Ford, McRobert, & Williams, 2013). Neurophysiological techniques, such as transcranial magnetic stimulation (TMS), electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) can be employed to identify and relate areas of brain activity to performance (e.g., Balser et al, 2014;Dennis, Rowe, Williams, & Milne, in press;Wright, Bishop, Jackson, & Abernethy, 2010. Psycho-physiological measures such as pupil diameter, inter-beat heart rate intervals, electromyography (EMG), and galvanic skin response may be recorded to examine changes in mental effort or stress/anxiety as a function of skill on the task (e.g., Vater, Roca, & Williams, 2015).…”
Section: 2mentioning
confidence: 99%